Metamorphism Trend in Some Mongolian Coals Revealed by Raman Spectroscopy - Sambuu, Munkhtsetseg; Ragchaa, Galbadrakh; Lkhamsuren, Enkhtur (Scientific transaction of the National University of Mongolia. Physics, 2022)
Raman scattering spectra of the representative samples from Mongolian low metamorphic coal deposits as of Sharyn-Gol, Baganuur, Nalaikh, Alagtolgoi and Dovt were measured. Total carbon content of these samples was measured by X-ray microanalysis method. An existence of graphite-like domains in vitrinite of the low metamorphism coals has been revealed by the Raman measurements. A Raman amorphous A band at 1342-1364 cm-1 is less intense and broader than that of a graphitic G band at 1560-1580 cm-1 for all studied samples. The graphitic G band is found to be shifted to higher frequencies within 1560-1580 cm-1 with a decrease of coal maturity, while the Raman amorphousgraphitic band intensity ratio R=fA/fG is found to be increased.